Monomicrobial Klebsiella pneumoniae Necrotizing Fasciitis With Liver Abscess: A Case Report and Literature Review. (March 2017) - Chen, Ching-En; Shih, Yu-Chung
Abstract : Background: Necrotizing fasciitis is one of the most life-threatening soft tissue infections and usually follows a major or minor trauma. Published reports regarding single microorganism liver abscess caused by Klebsiella pneumoniae in Taiwan indicate a septic metastasis rate about 12%. Although a hematogenous origin of necrotizing fasciitis from a liver abscess is rare in Taiwan, it remains possible in our clinical practice. Case Presentation: A 75-year-old man with a history of diabetes and liver abscess had a status of postdrainage 5 years earlier. The patient presented with elevated body temperature, swelling, and pain over the left hand and forearm for 4 days before coming to our emergency room. We performed a fasciotomy procedure under the preliminary diagnosis of necrotizing fasciitis. The patient's blood cultures yielded K. pneumoniae, and therefore recurrence of liver abscess was confirmed by ultrasonography. After treating with percutaneous drainage and third cephalosporin intravenously, the patient recovered and discharged on the 50th day after admission. Conclusions: Necrotizing fasciitis is a life-threatening soft tissue infectious disease. Once K. pneumoniae is identified both in blood and wound cultures of a diabetic patient with necrotizing fasciitis, it is recommended that the metastatic lesions undergo complete abdominal evaluation by the hematogenous route.